Simulations of a New Design Concept for Hybrid Ladder Filters - Wagner, Michael; Gossmann, Timo; Tomasik, Jakob; Weigel, Robert; Hagelauer, Amelie Marietta (2019 IEEE 20th Wireless and Microwave Technology Conference, WAMICON 2019, 2019)
In this paper, a new concept from circuit design perspective is presented and evaluated based on simulations. The concept allows for manipulation of the fixed behavior and limited effective electromechanical coupling factor (k-eff^2) of acoustic-wave resonators by additional lumped-element resonators. This hybrid approach enables resonance spreading of single acoustic-wave resonators and can be used for wide-band filter designs. A theoretical description of the concept is given and its benefits and application to filter design are outlined. Important characteristics are illustrated by a design example.
CRIS-Team Scopus Importer:2019-08-06